Design of novel inhibitors targeting the mutated protein of alpha synuclein using computational approach - SOUMYAKANTA PANDA; PRAVEEN KUMAR GUTTULA (International Journal of Pharma and Bio Sciences, 2017)
Researchers have discovered that the indication of Parkinson disease-Clumps of a protein Alpha synuclein, which are also called lewy bodies.Alpha synuclein(SNCA) has been believed to be a useful strategy for the treatment of Parkinson disease (PD) at a molecular level. However, no effective alpha synuclein inhibitors are currently available for this proteins. But In this current inspection, the mutated structure of alpha synuclein was modeled by using the present crystal structure of human alpha synuclein(PDBID-1XQ8). A structure-based pharmacophore model was developed based on the available crystal structure of alpha synuclein(1XQ8) with the two reported antioxidants, i.e., MitoquinoneMesylate (PubchemID:11388331) and Ubiquinone-10 (PubchemID:5281915).The best pharmacophore model consisted of 2 hydrogen bond donor and one hydrogen bond acceptor. The pharmacophore model was then used as a 3D-query in virtual screening to determine potential hits from DrugBank database.Finally, 27 hits were identified as potential inhibitors which were further validated by Molecular docking with the help of VlifeMDS software package.